2018
DOI: 10.1159/000485519
|View full text |Cite
|
Sign up to set email alerts
|

Tips, Tricks, and Advantages of 27-G Vitrectomy

Abstract: Purpose: We present the advantages and technique variations of 27-G vitrectomy in a variety of surgical retina cases. Methods: Patients with epiretinal membrane, retinal detachment, and proliferative diabetic retinopathy with vitreous hemorrhage and tractional detachments underwent 27-G vitrectomy. We present technique tricks, solutions to various problems and pitfalls, and the advantages of 27-G vitrectomy. Results: Postoperative visual acuity improved significantly in all patients. Anatomical restoration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…Our anatomic success rate of 93% is similar to previously reported results [ 2 ]. In addition, we observed a low rate of complications for other vitrectomy indications, in keeping with prior reports [ 25 ]. The macular hole closure rate observed in the present study is consistent with previous reports [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our anatomic success rate of 93% is similar to previously reported results [ 2 ]. In addition, we observed a low rate of complications for other vitrectomy indications, in keeping with prior reports [ 25 ]. The macular hole closure rate observed in the present study is consistent with previous reports [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our main modifications were introducing self-sealing scleral flaps, reducing the 23 G sclerotomies to 27 G (externalizing the anchors) and moving the sclerotomy sites slightly from the 3 and 9 o'clock position to the 2 and 8 o' clock 15 Enghelberg, and Chalam. 16 Reducing the sclerotomies to 27 G that are used to externalize the haptics should not only increase the hold ability but also prevent postoperative hypotony in a sutureless approach as was shown for 27 G vitrectomy both by Anastasilakis et al 17 and Naruse et al 18 It is noteworthy that we recently had to explant one Carlevale IOL. In cases where an explantation of the IOL is necessary, the anchors can simply be pulled back using a forceps and the IOL can be folded and explanted by a tunnel incision of 2.4 mm.…”
Section: Discussionmentioning
confidence: 90%
“…Reducing the sclerotomies to 27 G that are used to externalize the haptics should not only increase the hold ability but also prevent postoperative hypotony in a sutureless approach as was shown for 27 G vitrectomy both by Anastasilakis et al 17 and Naruse et al 18 It is noteworthy that we recently had to explant one Carlevale IOL. In cases where an explantation of the IOL is necessary, the anchors can simply be pulled back using a forceps and the IOL can be folded and explanted by a tunnel incision of 2.4 mm.…”
Section: Discussionmentioning
confidence: 92%
“…Regarding MIVS for PDR treatment, most people believe that a smaller VP can more easily enter the gap below the proliferative membrane to achieve an accurate operation. However, some studies have shown that the traditional 27G vitrectomy system does not have many advantages over other systems [ 14 17 ]. The vitrectomy technique for PDR patients still needs further development.…”
Section: Discussionmentioning
confidence: 99%